Myopathy due to juvenile acid maltase deficiency affecting exclusively the type I fibres. Issue 2 (February 1984) - Papapetropoulos, T; Paschalis, C; Manda, P
Abstract : The clinical and laboratory findings of a patient with juvenile acid maltase deficiency are presented. The patient died from respiratory muscle weakness at age 31 years. Muscle biopsy shortly prior to his death showed remarkable vacuolation affecting exclusively type I fibres and mild myopathic changes of both types of muscle fibres, while the muscle biopsy at age 26 years had shown no evidence of acid maltase deficiency.